Post-depositional behaviour of mercury and arsenic in submarine mine tailings deposited in Buyat Bay, North Sulawesi, Indonesia. (June 2018) - Shepherd, Thomas; Rumengan, Inneke; Sahami, Ali
Abstract: The post-depositional geochemical behaviour of mercury and arsenic in submarine mine tailings from the Mesel Gold Mine in Buyat Bay, North Sulawesi, Indonesia was assessed by in situ sampling of tailings porewaters using dialysis arrays and seawater and fish monitoring. Under steady-state conditions one year after cessation of tailings discharge, the calculated arsenic efflux incrementally added 0.8 μg/L of arsenic to the overlying seawater. The mercury efflux across the tailings-seawater interface was negligible. The arsenic and mercury concentration in seawater bottom samples monitored biannually during a 9-year post-closure program were 1.54 μg/L and <0.05 μg/L, respectively. Analysis of 650 fish tissue samples, from the post-closure monitoring had mean mercury and arsenic concentrations consistently below the FAO/WHO CODEX, and Australian and New Zealand National Food Standards, respectively. The results of the porewater, seawater and fish tissue demonstrate that the arsenic and mercury-bearing bearing compounds in the tailings are geochemically stable. Highlights: Research investigated the geochemical stability of the in-situ arsenic and mercury in submarine tailings minerals. Tailings porewater quality data used to conduct predictive modelling of the mobility of arsenic and mercury from tailings minerals. Long-term environmental monitoring of seawater quality and fish tissue conducted to confirm mineral stability predictions. Research represents the first multi-year submarine tailings geochemical and environmental investigation in a tropic environment.